Aspectos neuromusculares e funcionais: diferença entre graus leve e moderado da osteartrite radiográfica do joelho - Petrella, Marina (Universidade Federal de São Carlos, 2015)
This study aimed to compare neuromuscular aspects, such as antagonist co-activation during knee extension (Coext) and flexion (Coflex), functional ratio of the maximum concentric hamstring strength to the maximum eccentric quadriceps strenght for knee flexion (Icon:Qexc), knee extensor torque in concentric (PTcon_ext) and eccentric (PTexc_ext) ways, the concentric knee flexor torque (PTcon_flex) and physical function, in different knee OA degrees. It was also objective of this dissertation investigate the center of pressure (COP) behavior (amplitude and velocity of the anterior-posterior and medial-lateral displacement) during a task involving eccentric quadriceps contraction, and the correlation between center of pressure and variables related to muscle performance and physical function. These objectives comprise two studies, with different methodologies. Study I: 20 subjects with knee OA (GOA) and 20 healthy subjects (GC) performed a postural stability evaluation, standing on two force platforms (Bertec Mod) with 45 degrees of knee flexion. PTcon_flex and PTexc_ext were evaluated in a speed of 90°/s. Subjects answered Physical Function and Stiffness subscales of the questionnaire Western Ontario MacMaster Universities Osteoarthritis Index (WOMAC). Intergroup statistical analysis shown that subjects of the GOA, compared to GC, had no difference in postural control parameters, had lower Icon: Qexc (p = 0.004) and poorer selfreported physical function (p = 0.00) and stiffness (p = 0.001). Antero-posterior COP displacement was moderately and negatively correlated with the physical function subscale (ρ = -0.480, p = 0.02). Antero-posterior COP speed was moderately and negatively correlated with the physical function WOMAC subscale (ρ =-0.52, p = 0,01) and stiffness WOMAC subscale (ρ = -0.44, p = 0.03). Study II: 20 subjects with knee OA grade II (GOAII), 15 with knee OA grade III (GOAIII) and 19 healthy subjects (GC) performed isokinetic knee extension and flexion at 60 °/s, simultaneously to the electromyographic assessment of muscles quadriceps (vastus lateralis, rectus femoris, vastus) and hamstrings (biceps femoris and semitendinosus). Subjects answered Physical Function WOMAC subscale and performed functional tests 30-s chair-stand test (STS30s), 40mfast-paced walk test (Caminhada40m) and a stair-climb test (Escada). After intergroup analysis, GOAII showed higher Coflex (p = 0.001), higher Icon:Qexc (p = 0.000), Σemgflex_flex (p = 0.000), lower PTcon_ext (p = 0:02) and PTexc_ext (p = 0.008) and worse self reported physical function (p= 0.000). In GOAIII were identified greater Icon:Qexc (p = 0.000), lower PTcon_ext (p = 0.000), PTexc_ext (p = 0.000) and PTcon_flex (p = 0.04), worse self-reported Physical Function (p = 0.000) and worse performance in the functional tests: STS30s Caminhada40m e Escada (p = 0.017 p = 0.000 and p = 0.001, respectively). There was no difference between the GOAII and GOAIII for all variables (p ≥ 0.05). Together, these results suggest a neuromuscular adaptation present in individuals with knee OA, justifies the need for intervention from the early degrees of the disease and highlight the importance of taking into account different forms of assessment of physical function.
Keywords: Osteoartrite; Joelhos; Controle postural; Pico de torque; Dinamometria isocinética; Eletromiografia; Knee osteoarthritis; Postural control; Isokinetic dynamometer; Electromyography; Physical function; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL